ANALISIS KEBUTUHAN: MEDIA INTERAKTIF LIVE BOOK DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN PEMAHAMAN SISWA - Hanifah Salma; Gilang Maulana Jamaludin (As-Sulthan Journal of Education, 2026)
The development of digital technology requires PAI learning in elementary schools to adapt to the current generation who tend to like interactive and audiovisual learning media. However, field facts state that PAI learning is still dominated by lecture methods and conventional media so that it is less able to increase students' interest and understanding. This research is present to analyze the need for the development of live book interactive media in PAI learning. The research method uses Research & Development (R&D) with the ADDIE model which is limited to the analysis stage. The research subjects consisted of teachers and students in grade VI of SDN Liangjulang VI, with collection techniques through questionnaires and interviews. The results of the study show that PAI learning is still dominated by conventional media, while the need for audiovisual-based interactive media is relatively high. Live book media is considered to be able to increase student motivation and understanding. Therefore, the development of live books is needed as a PAI learning innovation.